Decentralization and Corruption: Does Decentralization Lead to Corruption in Local Level in Nepal? - Ghimire, Dipesh Kumar (Molung Educational Frontier, 2018)
Federalism has been constitutionally uniting separate political communities in a limited by encompassing political community (Kincaid and Tarr 2005). Federalism as a mode of governance is concerned with combining 'self-rule and shared rule' (Elazar, 1987), where by the constituent members of the federal union can govern themselves autonomously while they and their citizen also participate together in the common national governing regime, which is autonomous within its sphere of constitutional authority (Kincaid, 2011). Federalism is the extreme form of decentralization. Similarly, corruption is defined as exercise of official powers against public interest or the abuse of public office for private gain. Corruption is a symptom of degeneration of the relationship between the state and the people, characterized by bribery, extortion and nepotism (Altas, 1968). Similarly, Sen (1999) defines corruption or corrupt behavior as "the violation of established rules for personal gains and profits". This article tries to explore the relationship among federalism, decentralization and corruption. My finding is: constitutional, political and spatial decentralization is very strong and fiscal decentralization is very weak in Nepal. Fiscal decentralization plays vital role to improve quality of governance. However, lack of proper fiscal decentralization and highly constitutional, political and spatial federalism or decentralization promote corruption in the local level. Similarly the monitoring mechanism and vertical controls system are very weak in Nepal. It shows that the localization process motivate to corrupt behavior among public authorities.